LAMANYA PAPARAN KARBON MONOKSIDA TERHADAP PROFIL ENZIM ALANIN AMINOTRANFERASE - Sunita, Raden (UNIVED Press, Universitas Dehasen Bengkulu, 2018)
Background: Carbon Monoxide (CO) is a gas compound that is colorless, odorless and tasteless. Carbon monoxide comes from incomplete combustion such as burning firewood.Firewood is the main fuel used in tofu manufacturing in tofu factories. Wood-burning smoke in the tofu plant contains CO gas capable of polluting the air, so it can cause disturbance in the form of reddish eyes, quick thirst, headache and shortness of breath. This disorder can occur in exposed to factory workers who are exposed to CO. Carbon Monoxide enters the body at a certain level of exposure causing changes in some of the body's molecules and ultimately disrupts the functioning of the body. One of the organs involved changes due to excessive CO exposure is the liver characterized by increased levels of enzyme Alanin Aminotransferase (ALT). Research Objectives: To analyze the duration of carbon monoxide exposure to the enzyme profile Alanin Aminotranferase. Method: Using Cross Sectional design with 34 respondents. serum of factory workers know checked ALT levels using Mindray BA-88Aspeculator. Data were analyzed using Spearman Correlation test. Result: Exposure time of CO to factory worker to know obtained mean (4.06 years), median (4.00 years), minimum value (1 year) and maximum (7 years). Levels of ALT enzyme in factory workers know obtained mean (33,82 U / L), median (33.00 U / L), minimum value (8 U / L) and maximum value (56 U / L). There is a long relationship of CO exposure to ALT levels (r = 0.783; p <0.001; n = 34). Conclusion: The longer the factory workers know exposed to CO, the higher the ALT level. Factory workers know to reduce carbon monoside exposure by changing jobs and pay attention to the use of personal protective equipment when working.